The lady meets her match - Conkle, Gina (Conkle, Gina. Midnight meetings., 2015)
"Finding her is only half the battle. Cyrus Ryland didn't become England's wealthiest bachelor by being a pushover, but the mysterious beauty he discovers sneaking around at his grand ball enflames his curiosity. When the clock chimes midnight and she's nowhere to be found, Cyrus vows to scour all of London to uncover who she is. Little does he know that not only does Claire Mayhew not want to be found, but she wants nothing to do with him at all"--Page [4] of cover.